2005
DOI: 10.1177/172460080502000407
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase-3 (MMP-13) Expression in Cutaneous Malignant Melanoma

Abstract: MMP-13 appears to be a factor associated with tumor aggressiveness in CMM. It seems to eliminate an important barrier not only against tumoral invasion but also against proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…However, it may also act as a potent gelatinase by degrading a wide variety of extracellular matrix components (30,31). MMP-13 is overexpressed in a variety of tumors from such as head and neck, laryngeal, breast, chondrosarcoma, gastric, colorectal, vulvar carcinomas and cutaneous malignant lymphoma (17,(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…However, it may also act as a potent gelatinase by degrading a wide variety of extracellular matrix components (30,31). MMP-13 is overexpressed in a variety of tumors from such as head and neck, laryngeal, breast, chondrosarcoma, gastric, colorectal, vulvar carcinomas and cutaneous malignant lymphoma (17,(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…12,16 MMP13 seems to be related to an aggressive phenotype of melanoma. 17,18 In contrast to MMP2, MMP9 and MMP21 seem to have a more essential function in early events of melanoma formation and are downregulated in invasive stages. 18,19 In parallel to extracellular matrix degradation, adhesive characteristic of tumour cells during melanoma progression is changing.…”
mentioning
confidence: 99%
“…Compared to patients with negative-to-moderate MMP2 expression, patients with high MMP2 levels have significantly lower survival rates, and this information could predict patient survival, independent of tumor thickness and ulceration (48). Other studies have shown that higher MMP13 expression, which belongs to the collagenase group, is notably associated with metastasis and poorer survival of melanoma patients (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Although MMP13 is also gelatinolytic and type IV collagenolytic, it is prone to degrading type I, II and III collagens (25). Previous studies have shown that upregulated MMP13 and its activity in melanoma cell lines are involved in the metastasis of melanoma (26,27). A recent study revealed that MMP13 not only cleaves laminin-5 into small fragments to accelerate tumor metastasis but also disrupts vasculogenic mimicry in the presence of cleaved laminin-5, exerting dual effects on melanoma (28).…”
Section: Introductionmentioning
confidence: 99%